Multi-Locus Sequence Typing of Bartonella bacilliformis DNA Performed Directly from Blood of Patients with Oroya's Fever During a Peruvian Outbreak - Pons, MJ (2016)
Bartonella bacilliformis is the etiological agent of Carrion’s disease, a neglected tropical poverty-linked illness. This infection is endemic of Andean regions and it is estimated that approximately 1.7 million of South Americans are at risk. This bacterium is a fastidious slow growing microorganism, which is difficult and cumbersome to isolate from clinical sources, thereby hindering the availability of phylogenetic relationship of clinical samples. The aim of this study was to perform Multi Locus Sequence Typing of B. bacilliformis directly in blood from patients diagnosed with Oroya fever during an outbreak in Northern Peru.